Why violence against women is such politically controversial issue? The Polish struggle to ratify the Istanbul Convention (Biuletyn Kryminologiczny, 2013)
Gender-based violence and Violence Against Women is well known and empirically documented phenomenon that nowadays in criminology and human rights’ discourse does not raises any doubt. Gender-based violence in every of its each manifestation is a good example of cultural violence. Yet it took feminists and human rights advocates several years to have VAW and domestic violence recognized by public authorities as matter of public concern and action.